Strengthening Partnership : ICT Academy APTIKOM - HUAWEI - Tiawan Tiawan; Achmad Benny Mutiara; Rayi Pradono Iswara; Husni Teja; Solikin Solikin; Yunita Anggraini; Ismiyati Ismiyati; Saepul Aripiyanto; Eliza Ariesta; Surjandy Surjandy; Merios Gusan Putra; Radit Suryana; Dani Lukman Hakim; Nilam Atsirina Krisnaputri; Arif Supam Wijaya; Mulya Agung (International Journal Of Community Service, 2025)
Through strategic cooperation between university and industry, the community service initiative "Strengthening Partnership: ICT Academy APTIKOM–Huawei" seeks to establish a long-lasting digital talent ecosystem in Indonesia. The initiative, which is being implemented under the APTIKOM network with active participation from Institut Teknologi Sains Bandung (ITSB), incorporates curriculum alignment, structured talent development pathways, and worldwide ICT certification. By connecting academic learning with real-world technical standards and enabling instructors and students to gain globally recognized competencies, the program fosters innovation in higher education. The collaboration supports the development of human capital in a sustainable manner that is in line with Golden Indonesia 2045 and Indonesia's national digital transformation strategy. Regarding global development alignment, this initiative directly promotes SDGs 17 (Partnerships for the Goals) through cross-sectoral engagement between universities, professional associations, and the ICT industry, and SDG 4 (Quality Education) through ICT-driven capacity building. The results show that collaboration-driven innovation can increase equal access to technology education across Indonesian higher education institutions, boost institutional capabilities, and speed up digital preparedness.